Successful Strategy in Creating Low-FODMAP Wholegrain Bread—Simple and Global - Aleksandra M. Torbica; Vesna Vujasinović; Uroš Miljić; Goran Radivojević; Bojana Filipčev; Milorad Miljić; Miloš Radosavljević (Foods)
Fermentable oligo-, di-, and monosaccharides as well as polyols (FODMAPs) came into focus following recent clinical studies confirming that they worsen the symptoms of several gastrointestinal disorders suffered by 40% of the general population. Currently; only the low-FODMAP diet is a valuable strategy to help relieve IBS symptoms; however; it is only a temporary solution due to the nutritional deficiency caused by avoiding high-FODMAP foods. At the same time; bakery products are an important part of the human diet worldwide and the key contributors to the high intake of FODMAPs; especially in their wholegrain form. Previous research has shown that reducing FODMAPs content has negative effects on the structures of dough and bread; as well as on sensory quality. Our innovative low-FODMAP wholegrain bakery products provide a unique solution for achieving a high-dietary-fiber intake without compromising the sensory appeal. The novelty of our work is that these experiments were the first to be performed based on known but unexploited facts about the superiority of the baker’s yeast enzymatic complex. A crucial reduction in FODMAP content (by more than 75%) was achieved via a simple alteration to the bread formulation (6% baker’s yeast and the addition of baking powder) and key process parameter values (40 °C and 60 min dough fermentation time) in conventional breadmaking technology.